The cloning of the virus envelope glycoprotein F of canine distemper virus expressed in Pichia pastoris - Tizzano, Marco Antonio (2020)
Canine distemper virus (CDV) is a pathogen which affects members of the Canidae family, causing an acute, often fatal, systemic disease. CDV is an RNA virus of the family Paramyxoviridae that contains two envelope glycoproteins: F and HA. In this study, we focused on the envelope glycoprotein F as the main target for neutralizing antibodies produced after infection or vaccination. The complete coding region of the protein (60 kDa) was expressed in the methylotrophic yeast Pichia pastoris, obtained in a recombinant form and secreted to the culture medium. Later, to analyze its immunogenicity, the protein was combined with an oily adjuvant and used to inoculate mice. The results provide evidence supporting a potential application of this recombinant protein as a subunit vaccine.